2013
DOI: 10.1016/j.midw.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

‘Midwives are the backbone of our health system’: Lessons from Afghanistan to guide expansion of midwifery in challenging settings

Abstract: the depth of midwives' contribution in Afghanistan - from increased maternal health care service utilisation to changing community's perceptions of women's education and professional independence - is overwhelmingly positive. Lessons learned can serve as a model to other low resource, post-conflict settings that are striving to increase the workforce of skilled providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
98
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 12 publications
2
98
0
2
Order By: Relevance
“…Four of the papers were discursive (Pons et al, 2002;Fullerton et al, 2011;The RESPOND Project, 2012;Usher et al, 2012) and three based on primary research (Akiode et al, 2010;Voetagbe et al, 2010;Turkmani et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of the papers were discursive (Pons et al, 2002;Fullerton et al, 2011;The RESPOND Project, 2012;Usher et al, 2012) and three based on primary research (Akiode et al, 2010;Voetagbe et al, 2010;Turkmani et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…International educators reported that national educators were sometimes reluctant to change their teaching methods and clinical practice (Pons et al, 2002;Akiode et al, 2010;Voetagbe et al, 2010;Fullerton et al, 2011;The RESPOND Project, 2012;Usher et al, 2012;Turkmani et al, 2013). For example, Usher et al (2012) reported that, despite multiple collaborations with educators and administrators from the Pacific Island region to update curriculum with regional competency standards, some educators failed to implement the recommended changes when they returned to their home country.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations